Leading through disruption: The role of transformational leadership in the digital age - Deske W. Mandagi; Danny I. Rantung; Douglass Rasuh; Reimond Kowaas (Jurnal Mantik, 2023)
Transformational leadership has emerged as a critical concept that can significantly influence organizational success in a rapidly evolving digital landscape. However, despite the increasing importance of this topic, there remains a noticeable research gap in the understanding of the dynamics and impact of transformational leadership in the context of the digital era. To address this research gap, a systematic literature review using a comprehensive selection of 25 scientific articles from Scopus database was conducted. The primary objective was to explore the consequences of transformational leadership in the digital age and gain insights into its implications for organizational effectiveness and success. The systematic review encompassed articles that discussed transformational leadership in the context of digital transformation. The selected articles were rigorously analyzed and categorized to extract valuable insights into various consequences of transformational leadership and the digital era. The findings shed light on the essential outcomes of a transformational leadership style, including employee motivation and performance, job satisfaction, organizational commitment which leads to innovation, adaptability and resilience, and organization’s commitment, which eventually contribute to organizational growh and performance. This study provides a comprehensive overview of the current state of knowledge regarding the role of transformational leadership in the digital age. It highlights the role of transformational leadership can navigate and thrive in the dynamic landscape of digital transformation